Comparison of oncological outcomes after open and laparoscopic re-resection of incidental gallbladder cancer. Issue 3 (24th December 2019) - Vega, E A; De Aretxabala, X; Qiao, W; Newhook, T E; Okuno, M; Castillo, F; Sanhueza, M; Diaz, C; Cavada, G; Jarufe, N; Munoz, C; Rencoret, G; et al.
Abstract: Background: The safety and oncological efficacy of laparoscopic re-resection of incidental gallbladder cancer have not been studied. This study aimed to compare laparoscopic with open re-resection of incidentally discovered gallbladder cancer while minimizing selection bias. Methods: This was a multicentre retrospective observational cohort study of patients with incidental gallbladder cancer who underwent re-resection with curative intent at four centres between 2000 and 2017. Overall survival (OS) and recurrence-free survival (RFS) were analysed by intention to treat. Inverse probability of surgery treatment weighting using propensity scoring was undertaken. Results: A total of 255 patients underwent re-resection (190 open, 65 laparoscopic). Nineteen laparoscopic procedures were converted to open operation. Surgery before 2011 was the only factor associated with conversion. Duration of hospital stay was shorter after laparoscopic re-resection (median 4 versus 6 days; P < 0·001). Three-year OS rates for laparoscopic and open re-resection were 87 and 62 per cent respectively ( P = 0·502). Independent predictors of worse OS were residual cancer found at re-resection (hazard ratio (HR) 1·91, 95 per cent c.i. 1·17 to 3·11), blood loss of at least 500 ml (HR 1·83, 1·23 to 2·74) and at least four positive nodes (HR 3·11, 1·46 to 6·65). In competing-risks analysis, the RFS incidence was higher for laparoscopic re-resection ( P = 0·038), but OS did not differ between groups. Independent predictors of worse RFS were one to three positive nodes (HR 2·16, 1·29 to 3·60), at least four positive nodes (HR 4·39, 1·96 to 9·82) and residual cancer (HR 2·42, 1·46 to 4·00). Conclusion: Laparoscopic re-resection for selected patients with incidental gallbladder cancer is oncologically non-inferior to an open approach. Dissemination of advanced laparoscopic skills and timely referral of patients with incidental gallbladder cancer to specialized centres may allow more patients to benefit from this operation. Graphical Abstract: Oncological extended resection is the optimal treatment for resectable incidental gallbladder cancer. The outcomes of a multi-institutional study of the safety and oncological efficacy of a laparoscopic approach are reported. Equal outcomes in selected patients